STUDI KASUS: PERENCANAAN SDM MENGGUNAKAN ANALISA BEBAN KERJA MENTAL DENGAN METODE NASA-TLX PADA BANK DAERAH XY - Gusria, Amarisma; Ufaira, Rifda Alda; Sulaiman, Jihan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The banking industry is currently facing numerous challenges due to the high level of competition from modern digital products and increasing external environmental demands. In response, Regional Bank XY has made efforts to maintain strong competitiveness by restructuring its organization as part of its Human Resource Planning (HRP). Unfortunately, the implementation of HRP has not been optimal, as it was not supported by standardized calculations such as a Workload Mental Analysis. As a result, many employees have complained about an uneven distribution of workload across various divisions, ultimately affecting employee well-being. Therefore, this study uses a qualitative approach with a pragmatic paradigm and employs a case study method. Data collection techniques used to explore the issue include interviews, observations, and document analysis. Participants in this study were selected using a random sampling technique, consisting of 20 employees from 5 different divisions, and were assessed using the NASA-TLX workload analysis method. The results show that 11 respondents experienced mental overload, with a NASA-TLX score > 80, 8 respondents were in the Optimal Load category; and 1 respondent was classified as underload with a score < 50. Based on these findings, it is recommended that regular mental workload analyses be conducted, along with the establishment of programs to collect and address employee complaints related to workload in a more systematic and responsive manner.Keyword: Human Resources Management, Mental Workload Analysis; NASA-TLX methodAbstrak: Industri perbankan saat ini sedang dipenuhi dengan tantangan karena tingginya daya saing kompetitor dengan produk digital modern dan tututan lingkungan eskternal. Upaya Bank Daerah XY untuk tetap memiliki daya saing yang tinggi adalah dengan melakukan restrukturiasi organisasi sebagai bagian dari Perencanaan Sumber Daya Manusia. Namun sayangnya pelaksanaan PSDM tersebut belum optimal karena tidak diiringi dengan perhitungan baku seperti Analisa Beban Kerja. Sehingga banyanya karyawan yang mengeluh adanya beban kerja yang tidak tersebar secara merata di berbagai divisi yang akhirnya mempengaruhi kesejahteraan karyawan. Oleh karena itu, penelitian ini menggunakan pendekatan kualitatif dengan paradigm pragmatis, dan jenis kualitatif studi kasus. Metode pengumpulan data untuk memperdalam permasalahan adalah wawancara, observasi, serta analisa dokumen. Partisipan pada penelitian ini diambil menggunakan teknik random sampling, terdiri dari 20 karyawan dari 5 divisi yang berbeda untuk dilakukan analisa beban kerja NASA-TLX. Hasilnya Terdapat 11 responden yang memiliki klasifikasi beban kerja mental overload dengan skor NASA-TLX >80, 8 responden di Optimal Load, dan 1 responden di klasifikasi underload dengan skor <50. Adapun Rekomendasi yang diberikan adalah melakukan analisa beban kerja mental secara rutin dan membuat program untuk menampung keluhan karyawan terkait pekerjaan agar ditindak lebih lanjut.Kata kunci: Manajemen Sumber Daya Manusia, Analisa Beban Kerja Mental, Metode NASA-TLX